Comparison of slot deformation in stainless steel and ceramic brackets during torque - A finite element analysis - Harikrishnan, Pandurangan; Magesh, Varadaraju; Kingsly Jeba Singh, Devadhas (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: Torque in orthodontics is vital in final positioning of the teeth during fixed appliance therapy. Torqueing of archwiresis a significant factor in transferring the applied forces to the bracket which might cause deformation of the slot. Any deformation in the bracket slot can vary the torque prescription and thus can affect the tooth position.Aim: To evaluate and compare the deformation of stainless steel (SS) and ceramic bracket slots during torque, using finite element analysis.Materials and methods: A maxillary right central incisor bracket (0.022 x 0.028 inch) dimensions were measured using a profile projector, and a finite element (FE) model was constructed. Bracket materials considered were stainless steel (SS) and ceramic. An SSrectangular archwire (0.019 x 0.025 inch) with angles of twist ranging from 5° to 40° was theoretically converted into torque. The bracket slot deformation was obtained at the top, middle and bottom locations using FE analysis.Results: There is a uniform increase in deformation in the bracket slot walls from torque of 9.7 to 77.62 Nmm except that there isa 100 percent increase in deformation when the torque changed from 38.81 to 48.51 Nmm. The top location in the gingival slotwall showed maximum deformation compared with middle and bottom slot positions in both the materials. The deformation of SSbracket slot was more than the ceramic bracket slot.Conclusion: This study showed that the bracket slot walls of both SS and ceramic brackets are subjected to deformation by application of torque and the maximum deformation was in the upper part of the bracket slot.